Dialogue journal writing with nonnative English speakers : - Peyton, Joy Kreeft (Teachers of English to Speakers of Other Languages, 1990)
This book is the second language classroom, dialogue journals are a teaching tool that can be used with students in any classroom. The samples of dialogue journal writing in the book are from ESL classes at American schools where immigrant students are learning.